Strengthening indigenous resguardos in the Colombian Amazon - Recommendations for CSOs - Hammen, M.C. van der; Rodríguez, C. (2020)
As part of a multi-country review of community forest rights, Tropenbos Colombia conducted a review to better understand the role and potential of resguardos as mechanisms for decentralised forest governance. In this policy brief we summarize some of the main outcomes of the review, and the consequent recommendations for CSOs.